In Vitro Anti-inflammatory Activity Test of Ethanol Extract of Red Dragon Fruit Peel (Hylocereus polyrhizus) - Wima Anggitasari; Iski Weni Pebriarti; Lindawati Setyaningrum; Sholihatil Hidayati; Dyan Wigati; Aninda Fellisya Wibowo (Jurnal EduHealth, 2025)
Dragon fruit peel contains several compounds that have high antioxidant activity. Oxidative stress, which is one of the triggers for inflammation, is a problem to this day. Red dragon fruit skin contains various antioxidant compounds such as flavonoids and polyphenols. It is hoped that the presence of these antioxidant compounds can also have anti-inflammatory activity. This study aims to examine the anti-inflammatory activity of red dragon fruit skin using the red blood cell stabilization method. The test results showed that the ethanol extract of red dragon fruit peel with a concentration of 1000 ppm had the largest percentage of red blood cell hemolysis protection in induced hypotonicity, namely 92.596%. From these results it can be concluded that the ethanol extract of red dragon fruit peel has potential as an anti-inflammatory by stabilizing red blood cell membranes.